The Design of Domestic Wastewater Treatment Plant with Anaerobic - Aerobic System: Indonesia - Indra Ajiyanto; Nurhayati (FT-USNI, 2026)
Industrial sector growth inevitably requires proper domestic wastewater management. At PT. X, warehousing activities produce 3.13 m³/day of domestic wastewater from 33.33 m³/day of clean water usage. This wastewater originates from toilets, prayer rooms, and building maintenance, containing pollutants such as BOD, COD, TSS, ammonia, oil & grease, total coliform, and pH. This study aims to design a wastewater treatment system tailored to the wastewater characteristics and field conditions, using a combination of anaerobic and aerobic processes. A qualitative descriptive method was applied, with purposive sampling used to collect wastewater samples from operational facilities. The proposed WWTP consists of eight treatment stages, designed based on retention time and pollutant load to ensure optimal efficiency. Results showed pollutant reduction rates of 85% BOD, 85% COD, 90% TSS, 98% ammonia, 95% oil & grease, and 99.99% total coliform. The study concludes that a WWTP with a capacity of 5 m³/day is required to treat 3.13 m³/day of domestic wastewater